THE REQUIREMENT OF FLEXURAL REINFORCEMENT AREA BETWEEN SQUARE BEAM AND T BEAM BASED ON THE VARIATION OF STEEL YIELD STRENGHT - Samuel Layang (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
The purpose of this study is to determine the requirement of flexural reinforcement area between square beams and T beams. This study is using a space frame as a model with geometric shapes and symmetric loading. The requirement of flexural reinforcement needs is reviewed on the selfweight of structures, live loads and combined loads with the variations of steel yield strenght (fy) of 300 MPa, 350 MPa and 400 MPa. The result of this study indicate that the calculation of the requirement of the flexural reinforcement area which only takes into account the selfweight of the structure or live load gives the same result for square beams and T beams. However it gives different results for the combination load. The requirement of the flexural reinforcement area for T beam is 4% less than square beam. The analysis result is showing that the higher quality of steel used the needs of the area of reinforcement will reduce. The reduction that occurs for each variation of steel yield strength both on square beams and T beams is about 16.67%.